FRI0238 Increased Serum Free Light Chains of Immunoglobulins in Systemic Sclerosis Patients: Correlation with Lung Involvement and Inflammatory Milieu. (15th July 2016) - Bosello, S.L.; Basile, U.; De Lorenzis, E.; Canestrari, G.; Parisi, F.; Rucco, M.; Birra, D.; Gulli, F.; Napodano, C.; Pocino, K.; Forni, F.; Tolusso, B.; et al.
Abstract : Background: Humoral immunity and B cells are thought to play an important role in the pathophysiology of the systemic sclerosis (SSc). The production of free light chains (FLC) of immunoglobulins is abnormally high in different pathological autoimmune conditions and reflects B cell activation. Furthermore FLCs demonstrated different biological activities including their capability to modulate the immune system, proteolytic activity, complement cascade activation, as well as FLC binding to antigens and chemotactic factors. Objectives: To determine the FLC levels in patients with SSc and in healthy controls and to study their possible association with organ involvement and disease characteristics. Methods: Sixty-five SSc patients (90.0% females; mean age 50.8±17.0 years; 27 (41.5%) with diffuse skin involvement-dcSSc) and 20 age and sex matched healthy controls (HC) were studied. Clinical and immunological inflammatory characteristics were assessed for all the SSc patients. FLC levels were quantified by nephelometry (Freelite TM Human Kappa and Lambda Free Kits, The Binding Site, UK). IL6 and BAFF levels were measured in SSc patients by ELISA. Results: The mean serum FLC-κ level (SSc: 20.4±7.5 ng/ml vs HC 9.4±4.3 ng/ml, p<0.001) and FLC ratio (SSc: 1.6±0.6 vs HC 0.8±0.2, p<0.001) were significantly higher in patients with SSc compared to healthy controls, while the serum FLC-λ levels were comparable (SSc: 13.6±4.8 ng/ml vs HC 11.9±6.2 ng/ml, p=ns). The levels of FLC were comparable in patients with diffuse skin disease and limited skin involvement, while FLC-κ levels were increased in patients with restrctive lung (FVC<79%) disease (SSc: 26.4±7.4 ng/ml) when compared to patients with FVC>79% (HC 19.6±7.3 ng/ml, p=0.009). In SSc patients the levels of serum FLC-κ level directly correlate with the IL-6 levels (R=0.6, p<0.001), while no correlation was found with skin involvement and autoantibodies distribution. Conclusions: Free light chains of immunoglobulins (sFLC) levels are elevated in systemic sclerosis. High levels of sFLC are associated with the fibrotic lung involvement and with an higher degree of inflammation, supporting the role of B cell activation in the pathophysiology of SSc. Disclosure of Interest: None declared